2018
DOI: 10.1177/0886260518758333
|View full text |Cite
|
Sign up to set email alerts
|

“We Boil at Different Degrees”: Factors Associated With Severity of Attack in Sexual Killing

Abstract: Degree of injury, as measured by the Homicide Injury Scale (HIS), was examined to advance understanding of the dynamics of sexual killing. A total of 350 nonserial, male sexual killers were included, and the different ways that the sexual element of their offenses and the act of killing were connected was accounted for by determining that cases were either directly sexual (the sexual element and killing were closely bound), or indirectly sexual (killing was not a source of sexual stimulation). The two groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This suggests that these perpetrators are either again more skilled at using it or it is a more successful precaution although in the latter case the results would be somewhat inconsistent with the results obtained by Beauregard and Martineau (2014) who found that acting upon victim increased the chances of the case being solved. In the discussion regarding ‘overkill’, Stefanska, Higgs, Carter, and Beech (2018) noted that it is not possible to always define excessive violence as stemming from anger given that in some cases the severity of the attack could also represent more sadistic acts as indicted by Radojevic et al (2013). Similarly, it is possible that the ‘acting upon victim’ variable has been confounded with a sexual aspect of the case, that is, the behaviour is in fact not measuring forensic awareness but rather forms an intrinsic part of the offender’s sexual fantasy.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these perpetrators are either again more skilled at using it or it is a more successful precaution although in the latter case the results would be somewhat inconsistent with the results obtained by Beauregard and Martineau (2014) who found that acting upon victim increased the chances of the case being solved. In the discussion regarding ‘overkill’, Stefanska, Higgs, Carter, and Beech (2018) noted that it is not possible to always define excessive violence as stemming from anger given that in some cases the severity of the attack could also represent more sadistic acts as indicted by Radojevic et al (2013). Similarly, it is possible that the ‘acting upon victim’ variable has been confounded with a sexual aspect of the case, that is, the behaviour is in fact not measuring forensic awareness but rather forms an intrinsic part of the offender’s sexual fantasy.…”
Section: Discussionmentioning
confidence: 99%
“…To be considered as sexual, a homicide had to present at least one of the following characteristics at the crime scene: victim’s attire or lack of attire; exposure of the sexual parts of the victim’s body; sexual positioning of the victim’s body; insertion of foreign objects into the victim’s body cavities; evidence of sexual intercourse; evidence of substitute sexual activity, interest or sadistic fantasy. As the FBI definition has been criticized for potentially presenting false positives (Beauregard and Martineau, 2016; Kerr et al , 2013; Stefanska et al , 2018), all cases included in SHIelD present at least two criteria of the sexual homicide definition.…”
Section: Methodsmentioning
confidence: 99%
“…This finding suggested that some organized sexual murderers perpetrated overkill to prevent the identification of the victim’s identity (Beauregard and Martineau, 2016). Moreover, previous studies suggested that overkill in sexual homicide is not always the outcome of anger and impulsivity (Radojević et al , 2013; Stefanska et al , 2018). Stefanska et al (2018) identified that a high level of violence could also be associated with both direct (i.e.…”
Section: Overkill In Sexual Homicidementioning
confidence: 99%
See 2 more Smart Citations